Effect of NiS nanosheets on the butanone sensing performance of ZnO hollow spheres under humidity conditions - Perfecto, Tarcísio M. [UNESP]; Zito, Cecilia A. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2021)
Developing a device or material to detect volatile organic compounds (VOC) is no longer a challenge, despite its great interest. The difficulty is linked to developing a material that does not suffer from interferences, such as humidity, other gases, or volatiles present in the analyzes. In this sense, we present a new way to modify zinc oxide (ZnO) hollow spheres with nickel (II) sulfide (NiS) nanosheets, a barely studied material in the literature, to increase the butanone selectivity and to reduce the negative effect of humidity in the final response of the sensor. The ZnO hollow sphere (H-ZnO) was synthesized via a microwave-assisted solvothermal method followed by calcination. The NiS-H-ZnO heterostructures were produced by the deposition of NiS nanosheets on H-ZnO using thioacetamide and nickel (II) acetate tetrahydrate as NiS precursors. Under dry conditions, pure H-ZnO presents the best sensing response of 705.3 to 100 ppm of butanone followed by the 5%-NiS-H-ZnO heterostructure with a response of 123.8. However, the selectivity of 5%-NiS-H-ZnO improves and reaches a value of 12.92, which is more than four times higher than the selectivity of pure H-ZnO (3.12). Furthermore, the performance under humidity atmospheres shows that NiS heterostructures suffer less effect of the humidity. The responses to 100 ppm of butanone under 55% of relative humidity were 40.2 and 23.7 for 5%-NiS-H-ZnO and pure H-ZnO, respectively. Therefore, the developed butanone sensor demonstrated excellent response, selectivity, and a promising possibility for its practical use in sensing devices under real conditions of humidity.
Keywords: Butanone sensor; Chemoresistive; High selectivity; Metal sulfides; Nickel sulfide; NiS/ZnO heterostructure